BIOSAFTY ASSESSMENT OF Curcuma aromatica LEAF EXTRACT ON HISTOPATHOLOGICAL CHANGES IN KIDNEY OF ALBINO RATS UNDER THE STRESS OF ARSENIC TRIOXIDE - SHALINI ANAND,; PRABHU N. SAXENA, (International Journal of Pharma and Bio Sciences, 2016)
The purpose of this study was to investigate the impact of arsenic on kidney and its treatment with Curcuma aromatica to reduce arsenic toxicity. For experimental purpose wistar albino rats (100- 110g body weight) were divided into four groups (controlled, arsenic treated, Curcuma treated and arsenic + Curcuma treated group). Rats were given 0.15, 0.02, 0.01, 0.007 mg /100 gm body weight of arsenic and 50 mg/100 gm body weight of Curcuma orally after 1, 7, 14, 21 days respectively. The rats were etherised and the kidneys were carefully dissected out and processed for histological study. Many histopathological changes were observed in cortical region of kidney due to arsenic exposure whereas Curcuma aromatica leaf extract reversed such changes to near the control levels. Therefore it reveals the protective effect of Curcuma aromatica leaf extract under stressed condition of arsenic trioxide in albino rat.